HUBUNGAN EMPATI DENGAN HASIL UJIAN KETERAMPILAN KOMUNIKASI DOKTER-PASIEN DAN BREAKING BAD NEWS - Evelin Maharani Widjaja; Enny Irawaty (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2022)
Empathy is the ability to understand someone else’s experiences, emotions, and feelings. Empathy is one of the professional qualities in patient-centered health services. Empathy in medical education is closely related to the student's mastery of clinical competence. The student’s empathy measurement becomes crucial in acquiring feedback regarding empathy learning at the preclinical education stage. It encourages the study of the relationship between empathy and doctor-patient communication and breaking bad news (BBN) skill examination results. This study used a cross-sectional design on Faculty of Medicine students of Universitas Tarumanagara. Empathy was assessed using The Toronto Empathy Questionnaire while the results of the doctor-patient communication and BBN skills examinations were collected from the respondents via Google Form. In this study, the number of respondents was as many as 124 students with the majority of them being female (71.8%). A total of 78.2% of respondents possessed high empathy. A total of 94.4% of respondents passed the doctor-patient communication skills examination and 98.4% of respondents passed the BBN skills examination. Respondents who passed both of the examinations were 92.7%. Empathy and the results of the two clinical skills examinations were analyzed using Fisher's exact test which led to the discovery of a p-value >0.05. In this study, it can be concluded that there is no significant relationship between empathy and the results of the doctor-patient communication and BBN skills examinations on Faculty of Medicine students of Universitas Tarumanagara. Keywords: empathy, clinical skills, medical students Abstrak Empati merupakan kemampuan untuk memahami pengalaman, emosi, dan perasaan orang lain. Empati termasuk salah satu kualitas profesionalisme dalam pelayanan kesehatan yang berpusat pada pasien. Empati pada tahap pendidikan kedokteran berkaitan erat dengan penguasaan mahasiswa terhadap suatu kompetensi klinis. Pengukuran tingkat empati mahasiswa menjadi hal yang penting sebagai umpan balik terhadap pembelajaran empati pada tahap pendidikan pre-klinik. Hal ini mendorong untuk dilakukannya penelitian mengenai hubungan empati dengan hasil ujian keterampilan komunikasi dokter-pasien dan breaking bad news (BBN). Penelitian ini menggunakan desain cross sectional terhadap mahasiswa Fakultas Kedokteran Universitas Tarumanagara. Empati dinilai dengan menggunakan The Toronto Empathy Questionnaire serta hasil ujian keterampilan komunikasi dokter-pasien dan BBN ditanyakan ke responden melalui Google Form. Jumlah responden pada penelitian ini sebanyak 124 mahasiswa dengan mayoritas responden berjenis kelamin perempuan (71,8%). Sebanyak 78,2% responden memiliki empati tinggi. Sebanyak 94,4% responden lulus ujian keterampilan komunikasi dokter-pasien dan 98,4% responden lulus dalam ujian keterampilan BBN. Responden yang lulus pada kedua ujian keterampilan tersebut sebesar 92,7%. Empati dan hasil ujian kedua keterampilan klinis dianalisis dengan menggunakan uji Fisher’s exact dan didapatkan p value >0,05. Pada penelitian ini dapat disimpulkan bahwa tidak terdapat hubungan yang bermakna antara empati dengan hasil ujian keterampilan komunikasi dokter-pasien dan BBN pada mahasiswa Fakultas Kedokteran Universitas Tarumanagara.